On Professor Hahn's Tatonnement Stability Theorem: Comment and Example - Kagawa, Akio; Kuga, Kiyoshi (Review of Economic Studies, 1980)
Akio Kagawa, Kiyoshi Kuga; Notes and Comments: On Professor Hahn's Tâtonnement Stability Theorem: Comment and Example, The Review of Economic Studies, Volu